Plesionika sanctaecatalinae Wicksten, 1983 (Crustacea Decapoda Caridea Pandalidae) from off the west coast of Pacific Mexico - Hendrickx, Michel E. (Zootaxa, 2016)
A large series of specimens of Plesionika sanctaecatalinae was obtained during sampling operations off the west coast of the Baja California Peninsula in 2012 and 2014 (TALUD cruises). This material was examined and compared to the original description, the holotype and two paratypes. Although the fresh material fit well with the type material examined, some discrepancies were noted in the illustrations of the original description, particularly regarding scaphocerite and the telson, and new illustrations are provided. The series of sample available from the TALUD cruises allow to increase considerably the number of localities known for this species in the California Current area. A series of unpublished records corresponding to material examined in the original description but not listed in details, allows for further increase of the number of reported localities where P. sanctaecatalinae has been collected. Its vertical distribution in the water column, however, remains unclear due to the fact that no discrete samples are available for this species.